Merantau Culture as One of The Stratgeies in Developing Independent Character in The Environment Minangkabau Community - Denia Syapitri; Firman; Mohd Nazri Abdul Rahman (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2025)
For most Indonesian people, especially the Minangkabau tribe in West Sumatra, merantau has become a way of life. This culture of wandering is very significant and important in the archipelago. So the Minangkabau people use this culture of wandering as a strategy in cultivating an independent nature. This research aims to see and find out how the culture of wandering is a strategy in developing independent character in the Minangkabau community. The method used for this study is a literature study sourced from books, journals, papers, notes or articles to collect information about the culture of merantau Minangkabau society, independent character and the culture of merantau towards the development of independent character in the Minangkabau community. The research results show that merantau symbolizes Minangkabau cross-cultural culture, where they initially come into contact with different systems and ways of life. They have to learn to adapt if they want to adapt, be accepted even though there are differences and the Minangkabau people cultivate an independent character as one way of doing this.